Analysis of the Depth of Literacy with Fertility in Ever Married Women Aged 15-49 Years (Advannced Analysis of Indonesian Health Demographc Survey (SDKI) 2017) - Muslimin, Irma; Hamzah, Hadzmawaty (Indonesian Journal of Global Health Research, 2023)
Literacy is a concept that is integrated into knowledge, motivation and competence to access, understand, assess and apply health information to make decisions and make decisions in everyday life. One important factor that supports a person's knowledge is the depth of literacy. This research uses a quantitative approach using data from the results of data collection in the Indonesian Health Demographic Survey which is then analyzed using the chi-square test. The research results show that depth of literacy is related to fertility with p = 0.000, which means there is a relationship between depth of literacy and fertility level. The importance of literacy is the main trigger factor for increasing knowledge, so efforts need to be made so that people increase their interest in reading about things related to their health.